Gender and Tourism Motivations in Saudi Arabia - Mohammed Alkohaiz; Ibtisam A. Alamri; May H. Alhusayni; Abeer M. Bin Safran; Basem Hboubati; Hassan Ain (SAGE Open)
This study investigated whether the perceptions of Saudis toward tourism differ by gender in their motivations for engaging in domestic and international tourism. Data were collected through a survey of 1,536—769 men and 769 women—between 18 and 35 years of age to examine what motivates their engagement in tourism. In terms of domestic tourism, the results indicated gender differences in several areas of motivation. Women tended to favor events, festivals, pilgrimages and family gatherings more than men. In terms of international tourism, the study found that men were more likely than women to favor affordability, freedom from adherence to customs and traditions, and the formation of new friendships. Women showed more interest than men in getting to know different cultures.